Assessing the Attractiveness of Three Baits for Roof Rats in California Citrus Orchards - Kallista N. Wales; Ryan Meinerz; Roger A. Baldwin (Agronomy, 2021)
Roof rats (Rattus rattus) are common pests of tree fruit and nut orchards in California. Tracking tunnels are an effective and practical tool for monitoring changes in roof rat numbers in orchard systems, but they rely on the use of attractive baits to draw in rats to the tracking surface. The identification of baits that are both attractive and readily available would be of great assistance for monitoring changes in roof rat numbers within agricultural fields. Therefore, we tested the attractiveness of a soft bait (Liphatech Rat and Mouse AttractantTM), a wax block (Liphatech NoToxTM), peanut butter, and a control (i.e., no bait applied) to roof rats when applied within tracking tunnels. We did not observe a difference in visitation to any of the tested attractants, although all attractants yielded greater visitation rates than control tunnels. However, tracking tunnels without any attractant were still visited at a relatively high rate, indicating the tracking tunnel is attractive to roof rats. As such, monitoring tools that provide shelter may increase detectability, although this would need to be verified. Regardless, all three food-based lures we tested increased the attractiveness of tracking tunnels and could be used to increase visitation to these monitoring devices.